Tri Hita Karana and Tourism Village Management Models for Wellbeing - Ni Ketut Sari Adnyani; I Gusti Ayu Purnamawati (Target : Jurnal Manajemen Bisnis, 2020)
This study aims to analyze the traditional law community unit is examined by emphasizing the concept of Tri Hita Karana as a reference for village spatial planning, village buildings, and harmonization with cultural and environmental conservation in Penglipuran village. Based on field surveys, several attractions in Indonesia have not heeded the concepts of Tri Hita Karana, Tri Mandala, and Asta Kosala-Kosali. Sample of this study were the traditional village officers and associations of the Indonesian Hotels and Restaurants Association to test the model of the tourism village that imply the humanist integration of indigenous peoples empowerment. Statistical analysis is based on survey data and records of the amount of environmental damage due to high tourist activity. The results of this study shows that mutual humanist synergy is a collective nature of indigenous peoples and tourism service actors leading to environmentally friendly cultural ecotourism. The steady culture of the survival of traditions, customs, and ancestral culture has an impact on sustainable tourism development. The environmentally unconscious behavior becomes a challenge. Prevention of environmental damage can be overcome by offering a model of the Penglipuran tourism village as a universal model with environmental balance characteristics.